Some Features of Regional Policy in Turkestan - Normatov Otabek Maxamatjonovich (International Journal on Orange Technologies, 2021)
The zoning policy carried out in the Turkestan ASSR, from the 1922 very beginning had economic and administrative features. The Soviet government in 1923-1924, attracting to the zoning policy, in addition to the Turkestan ASSR, the Bukhara and Khorezm republics, on the one hand, sought to manage the economy of the entire Turkestan Territory from a single center and achieve economic efficiency, on the other hand, zoning was aimed at reviving and the development of a destroyed national economy. This article reflects general aspects of zoning policies. The development and implementation of the economic and territorial zoning of the Turkestan ASSR is analyzed based on historical sources